2019
DOI: 10.3390/metabo9040064
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre-Analytical Conditions on Blood Metabolomics in Epidemiological Studies

Abstract: Serum and plasma are commonly used in metabolomic-epidemiology studies. Their metabolome is susceptible to differences in pre-analytical conditions and the impact of this is unclear. Participant-matched EDTA-plasma and serum samples were collected from 37 non-fasting volunteers and profiled using a targeted nuclear magnetic resonance (NMR) metabolomics platform (n = 151 traits). Correlations and differences in mean of metabolite concentrations were compared between reference (pre-storage: 4 °C, 1.5 h; post-sto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
(83 reference statements)
5
13
0
Order By: Relevance
“…Samples were non-fasted and were not cooled during transport to the laboratory, which may have affected the results of the NMR metabolomics assay [ 41 , 42 ], albeit studies exploring the potential impact of pre-processing conditions on the specific metabolites measured using the Nightingale platform are scarce. One study has reported that most of the metabolites measured using the Nightingale platform in non-fasted serum samples were not materially affected by delaying processing for 48 h at 21 °C (experimental condition; conditions similar to those in the current study) compared to processing within 1.5 h at 4 °C (reference condition) [ 42 ]. For metabolites consistently showing up as different between diet groups in the current analysis, rank correlations between metabolite concentrations in samples kept at the experimental versus the reference condition were 0.7 or above, except for, tyrosine ( r = 0.6) and lipid traits in small HDL (ranging from 0.6 and 0.7).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were non-fasted and were not cooled during transport to the laboratory, which may have affected the results of the NMR metabolomics assay [ 41 , 42 ], albeit studies exploring the potential impact of pre-processing conditions on the specific metabolites measured using the Nightingale platform are scarce. One study has reported that most of the metabolites measured using the Nightingale platform in non-fasted serum samples were not materially affected by delaying processing for 48 h at 21 °C (experimental condition; conditions similar to those in the current study) compared to processing within 1.5 h at 4 °C (reference condition) [ 42 ]. For metabolites consistently showing up as different between diet groups in the current analysis, rank correlations between metabolite concentrations in samples kept at the experimental versus the reference condition were 0.7 or above, except for, tyrosine ( r = 0.6) and lipid traits in small HDL (ranging from 0.6 and 0.7).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research with this platform has observed that most metabolites (especially lipid related) are minimally affected by the prestorage and poststorage conditions tested. 41 Although we have data of many patients at our disposition, prediction of a complex and multicausal phenomenon like SCA might demand even bigger numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids were modelled in original units and as ratios (expressed in %) to total fatty acids. Details of this platform and its use in epidemiological studies have been described elsewhere [32,33,34,35,36]. In addition, we calculated the phenylalanine/tyrosine ratio as it was shown to be a marker of catabolism in individuals with anorexia nervosa [37,38].…”
Section: Methodsmentioning
confidence: 99%